AVRELIVS AVGVSTINVS: THE TESTIMONY OF THE OLDEST MANUSCRIPTS OF SAINT AUGUSTINE'S WORKS - Gorman, Michael M. (The journal of theological studies, 1984)
MICHAEL M. GORMAN; AVRELIVS AVGVSTINVS: THE TESTIMONY OF THE OLDEST MANUSCRIPTS OF SAINT AUGUSTINE'S WORKS, The Journal of Theological Studies, Volume 35, Issue